The effects of nutritional supplementation on older sarcopenic individuals who engage in resistance training: a meta-analysis - Song, Zixian; Pan, Tingting; Tong, Xu; Yang, Ying; Zhang, Ze (Frontiers in Nutrition, 2023)
Objective: Sarcopenia is a typical age-related disorder characterized by loss of muscle mass, strength, and physical function. Resistance training has a noticeable effect on sarcopenia, but there is no consensus on whether nutritional supplements can boost this effect. We conducted a meta-analysis of relevant literature to investigate the therapeutic effect of resistance training combined with nutrition intervention on sarcopenia compared with resistance training alone. Methods: Cochrane Library, PubMed, Web of Science, Embase, Sinomed, CNKI, VIP, and Wanfang Data were searched for relevant studies on resistance training combined with nutritional intervention for aging adults with sarcopenia. The retrieval period ranged from the inception of the databases to May 24, 2022. Literature screening and information extraction were performed by two researchers. The Physiotherapy Evidence Database (PEDro) scale was adopted for literature quality evaluation and Stata 15.0 software for analysis. Results: Twelve clinical trials were included, involving 713 older adults diagnosed with sarcopenia, of whom 361 were assigned to the experimental group and 352 to the control group. Compared with the control group, grip strength of the experimental group was substantially elevated [WMD=1.87, 95%CI (0.01, 3.74), P=0.049]. Subgroup analysis demonstrated that vitamin D and protein increased grip strength and gait speed. There were no significant improvement in grip strength and gait speed in the protein and vitamin D free subgroup. Conclusions: This meta-analysis demonstrated that resistance training combined with additional nutritional supplementation, especially compound nutritional supplements that included protein and vitamin D, might further enhance grip strength rather than muscle mass in older adults with sarcopenia.